Seasonal Variation of the Mountain Phytoplankton in the Arid Mendoza Basin, Westcentral Argentina - Peralta, Maria Patricia (2001)
We analyzed the seasonal composition of phytoplankton from the Mendoza River and its tributaries from the High Cordillera to the plain in centralwest Argentina. A total of 72 algae species were identified; among them,  36 species were diatoms, 17 chlorophytes, 15 cyanophytes, three euglenophytes and one pyrrophyte. A marked seasonality was observed. Diatoms were dominant in all seasons at most of the sampling sites, with abundance peaks in autumn and winter. Cyanophytes were found throughout the year but with highest numbers in summer and spring. Chlorophytes were well represented throughout the year except in winter. The pyrrophytes were represented by Peridinium gatunensis, which was recorded exclusively in the spring  along with the chlorophyte Staurastrum sebaldii at most of the sampling sites. Euglenophytes were found only in the lower basin and with maximum richness and density in autumn. Most of the diatoms were benthic. Nitzschia palea, Euglena proxima and E. oxyurus were limited to certain sectors of the river that receive sewage discharge. The remainder of the river is generally free from significant anthropogenic impact.